Comparing compost and vermicompost produced from market organic waste - Syarifinnur Syarifinnur; Yulia Nuraini; Budi Prasetya; Eko Handayanto (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study was to obtain suitable methods and the combination of market organic waste to make better organic fertilizer.Method The data were obtained experimentally in the decomposer room. The experimental design was a completely randomized design. The market organic waste consisted of comparing cabbage, banana peduncle, pineapple, added rice straw, and cow manure as bedding. The study used 12 treatments with three replicates. 4 treatments for composting methods (without earthworm) and 8 for vermicomposting (4 treatments using Lumbricus rubellus and 4 treatments using Eudrillus eugeniae). The compost and vermicompost characteristics variables were final weight, reduction, color, texture, and smell. The variables for chemical properties were pH, C-organic, Total Nitrogen, Total Phosphoros, and Total Potassium.Results Vermicomposting method reduced market organic waste higher than compost 48.67 to 58%. Vermicompost is black like soil and more crumble. C-organic, pH, total Nitrogen, total Phosphorous and total Potassium following quality of SNI 19-7030-2004. The results show the compost with the combination of cabbage and banana peduncle combination (C-T1) had better values on total N (1.95%) and Total K (4.96%). Vermicompost with the combination of banana peduncle and pineapple with Eudrillus eugeniae (E-T3) had better average values ​​on total P (0.43%). The combination of market organic waste used to produce organic fertilizers can be made on a small or larger scale.Conclusion Vermicomposting is an effective strategy to reduce market organic waste. Composting with T1 combination (C-T1) and vermicomposting T3 combination (E-T3) had better value and was recommended for the following research stage.